On applications of orbit codes to storage - Liu, Shiqiu (2016)
We consider orbit codes, namely subspace codes obtained from orbits of the action of subgroups of GLn(Fq) on m-dimensional subspaces of Fnq. We discuss their applicability to design storage codes, in particular in the context of collaborative repair: we identify known storage codes that can be interpreted as orbit codes, motivate why orbit codes provide good candidates for storage codes, and translate the storage code parameters into those of the algebraic objects involved. Two simple families of storage orbit codes are given.